Rheumatoid constrictive pericarditis - McRorie, E; Wright, R; Errington, M; Luqmani, R (1997)
A 73-yr-old woman with a 4 yr history of rheumatoid arthritis presented with the clinical features of congestive cardiac failure. She had a good early response to standard therapy although she subsequently developed recurrent biventricular failure. The preservation of good ventricular function on echocardiography in the face of clinical evidence of myocardial insufficiency raised the possibility of constrictive pericarditis, which was confirmed on cardiac catheterization. Constrictive pericarditis should be considered in patients with rheumatoid arthritis who develop unexplained cardiac failure. Early diagnosis requires a high index of suspicion and cardiac catheterization may be necessary to confirm the diagnosis. Medical treatment is largely ineffective and pericardiectomy should be considered.